Anti-neuronal and anti-mitochondrial autoantibodies are associated with lower functional status and more severe respiratory symptoms in post COVID syndrome - Vogelgesang, Antje; Steinmetz, Anke; Stufano, Angela; Schino, Valentina; Plantone, Domenico; Flöel, Agnes; Lucchese, Guglielmo (Frontiers in Immunology, 2025)
IntroductionWe previously identified IgG autoantibodies targeting epitopes within brainstem proteins—disabled homolog 1 (DAB1), apoptosis-inducing factor 1 (AIFM1), and surfeit locus protein 1 (SURF1)—as markers of severe acute COVID-19. This study investigates whether the same autoantibodies contribute to the pathophysiology of Post COVID Syndrome (PCS).MethodsUsing a multiplexed bead-based immunoassay, we measured IgG levels against 18 synthetic peptides derived from DAB1, AIFM1, and SURF1 in serum samples from 45 PCS patients and 30 post-COVID controls without long-term symptoms. We employed generalized linear mixed models (GLMM) and nonlinear principal component analysis (CATPCA) to explore associations between antibody levels and clinical variables, including functional status (PCFS), respiratory symptoms, fatigue, cognitive impairment (as assessed by the Montreal Cognitive Assessment, MoCA), and mood.ResultsHigher IgG levels against the three autoantigens significantly predicted PCS at 3 months postinfection (t=2.21, p=0.03), whereas antibodies against a control peptide (polio) showed no such association. CATPCA identified a principal component capturing respiratory symptoms and functional impairment (PCFS), which was also significantly predicted by autoantibody levels (t=2.04, p=0.04). MoCA scores did not correlate with autoantibody levels, and subjective cognitive complaints were paradoxically linked to lower antibody titers and fewer physical symptoms.ConclusionsThe findings from the present explorative study, although largely correlative, appear to suggest a sustained autoimmune response targeting neuronal and mitochondrial proteins in PCS, particularly associated with respiratory dysfunction and reduced functional capacity. The results also highlight potential limitations of standard cognitive screening tools like the MoCA in detecting subtle deficits in PCS. The identified autoantibodies may serve as biomarkers for persistent post-COVID disability. Future research replicating present results on larger samples and specifically investigating a causal link between occurrence of the Auto-Abs and PCS is needed for shaping future immunomodulatory therapeutic strategies.